2017
DOI: 10.3389/fpls.2017.01195
|View full text |Cite
|
Sign up to set email alerts
|

Root-Knot and Cyst Nematodes Activate Procambium-Associated Genes in Arabidopsis Roots

Abstract: Developmental plasticity is one of the most striking features of plant morphogenesis, as plants are able to vary their shapes in response to environmental cues. Biotic or abiotic stimuli often promote organogenesis events in plants not observed under normal growth conditions. Root-knot nematodes (RKNs) are known to parasitize multiple species of rooting plants and to induce characteristic tissue expansion called galls or root-knots on the roots of their hosts by perturbing the plant cellular machinery. Galls c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 59 publications
5
56
0
Order By: Relevance
“…The TDIF-TDR-WOX4 pathway promotes procambial cell proliferation, whereas the TDIF-TDR-Glycogen Synthase Kinase3-BRI1-EMS SUPPRESSOR1 pathway inhibits xylem differentiation from procambial cells. Procambial-associated genes are activated in both CN and RKN feeding sites (Guo et al, 2017;Yamaguchi et al, 2017). The TDIF-TDR-WOX4 procambial cell proliferation pathway is required for CN feeding site formation (Guo et al, 2017); however, further research is needed to assess whether the TDIF-TDR-Glycogen Synthase Kinase3-BRI1-EMS SUPPRESSOR1 signaling is equally important.…”
Section: Cle-like Peptidesmentioning
confidence: 99%
“…The TDIF-TDR-WOX4 pathway promotes procambial cell proliferation, whereas the TDIF-TDR-Glycogen Synthase Kinase3-BRI1-EMS SUPPRESSOR1 pathway inhibits xylem differentiation from procambial cells. Procambial-associated genes are activated in both CN and RKN feeding sites (Guo et al, 2017;Yamaguchi et al, 2017). The TDIF-TDR-WOX4 procambial cell proliferation pathway is required for CN feeding site formation (Guo et al, 2017); however, further research is needed to assess whether the TDIF-TDR-Glycogen Synthase Kinase3-BRI1-EMS SUPPRESSOR1 signaling is equally important.…”
Section: Cle-like Peptidesmentioning
confidence: 99%
“…Expression of the WOX, CLE, and PXY cambial activation pathway is also key to development of the gall-like structures elicited by root-knot and cyst nematodes and nodulation by Rhizobium in legumes 82 , suggesting that phylloxera and other parasites have converged on altering developmental regulation of vascular stem cells during gall elicitation. We are aware of no studies of CLE peptide production in phylloxera or other insects, as has been shown to be important for root-galling nematodes 82 .…”
Section: Sources Of Meristemmentioning
confidence: 99%
“…Phloem marker genes, such as SUC2, SEOR1 (AT3G01680), and APL (AT1G79430) (Kondo et al, 2016;Yamaguchi et al, 2017), were expressed at much higher levels in VS and almost not at all in MN ( Fig. 2; Supplemental Fig.…”
Section: Initial Characterization Of the Rna-seq Datamentioning
confidence: 99%